Use of labetalol in the treatment of severe hypertension during pregnancy. - Michael, C A (1979)
1 Labetalol, a hypotensive agent combining alpha- and beta-adrenoceptor antagonist properties, was used to treat severe hypertensive disease complicating pregnancy. 2 Effective reduction in BP was achieved in all but 3 of the 25 patients treated. Careful monitoring of feto-placental function was undertaken to ensure the maintenance of fetal well-being. Maternal and fetal side-effects were minimal and it was not necessary to discontinue the drug in any patient. 3 Labetalol was estimated in the cord blood of the fetus at delivery as well as in the breast milk of mothers on day 3 post partum. There were no adverse effects of the drug on the infants and significant hypotension did not occur. 4 The reults suggest that labetalol has a direct action on fetal lung maturation and this, together with its effective hypotensive effect, contributes to the low perinatal mortality (3.5%) observed. 5 Oculotoxicity due to the labetalol was not observed in the infants delivered. 6 It is concluded that the efficient hypotensive action of labetalol, together with apparent freedom from maternal and fetal side-effects, and consequent improved perinatal mortality, suggest that it is a suitable drug for use in pregnancy complicated by hypertension.